2008
DOI: 10.1590/s1415-52732008000100008
|View full text |Cite
|
Sign up to set email alerts
|

Gasto energético de repouso em pacientes com doença renal crônica

Abstract: O conhecimento do gasto energético de repouso é de fundamental importância na determinação das necessidades energéticas e, conseqüentemente, no estabelecimento das recomendações de energia de um indivíduo. O elevado gasto energético, se não compensado por uma ingestão alimentar suficiente, poderá contribuir para a desnutrição e o maior risco de morbidade e mortalidade. Nos pacientes com doença renal crônica, a uremia per se e o tratamento de diálise estão, freqüentemente, associados a vários distúrbios, como a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
14

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
4
0
14
Order By: Relevance
“…The main difference between REE and BEE is that REE is measured after the individual dislocation to the exam site, necessitating the prior resting period of 30 minutes to neutralize the effects of the physical activity performed [28]. Study found that REE is 10-15% higher than the BEE [29].…”
Section: Compher Et Al (2006)mentioning
confidence: 99%
“…The main difference between REE and BEE is that REE is measured after the individual dislocation to the exam site, necessitating the prior resting period of 30 minutes to neutralize the effects of the physical activity performed [28]. Study found that REE is 10-15% higher than the BEE [29].…”
Section: Compher Et Al (2006)mentioning
confidence: 99%
“…Considerando os benefícios do tratamento dialítico, que prolonga a vida dos pacientes com DRC, as condições impostas pela doença e pelo próprio tratamento provocam uma série de alterações sistêmicas, metabólicas e hormonais, que podem afetar adversamente a condição nutricional desses pacientes 5 . O processo de hemodiálise pode levar à remoção de 1 a 4 litros de fluido em um período médio de 4 horas, durante três dias da semana, e varia de paciente para paciente e da eficiência da diálise 4,5 .…”
Section: Introductionunclassified
“…(massa gorda,6±5,(5)(6)(7)(8)9±6,2%; p=0,620), (massa corporal magra, TF= 9,0±5,3% x TC= 6,8±6,7%; p=0,431) e no GER (TF= 19,6±15,3% x TC= 10,7±24,5%; p=0,331 …”
mentioning
confidence: 99%
“…2 , and there is a significant increase in the rates of obesity among the young 3 , a concerning finding due to the association of obesity with cardiovascular diseases and early death 4 . Th excessive accumulation of body fat may be mainly attributed to bad eating habits and sedentary lifestyle, resulting in a positive energy balance, which occurs when energy intake exceeds energy expenditure and leads to increased body fat 5 . Studies show that body composition variables have an important effect on energy metabolism 6 and that lean body mass (LBM) was the body compartment with the highest metabolic activity, explaining 73% of the variation in resting energy expenditure (REE) and 80% of the variation in overall energy expenditure 6 .…”
mentioning
confidence: 99%